Shark in the park - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (London : Usborne ; Tulsa, Okla. : EDC, 2002)
Pup mistakes Jake Snake for a shark in the park.
"A phonics reader"--Cover.
Lift-the-flap pages.
2.6.
2.6
2.6
K-3
Keywords: Toy and movable books -- Specimens; Animals -- Fiction; Stories in rhyme; Toy and movable books; Animals -- Fiction; Stories in rhyme; Toy and movable books; Toy and movable books